A resposta de andar na roda como reforço em ratos: um estudo exploratório sobre a resposta de andar na roda como reforço e sua relação com a restrição do tempo de alimento disponivel - Pedroso, Mariana Queiroz Martins (2005)
Replicating Iversen s (1993) procedure, this study s goal was to increase the comprehension of the running response of rats on an activity wheel when running was a consequence of responding on a fixed-ratio schedule. The study also explored the impact of a restricted period of food availability on the reinforcing value of wheel running. Body weight, food and water consumption of six female rats were systematically measured. Five subjects were also submitted to a procedure designed to install wheel-running as a consequence for lever pressing. After baseline measures of wheel running, a gradual restriction of the session time when wheel-running was possible was implemented, followed by the shaping of a lever pressing response reinforced by wheel-running, and a phase when lever pressing was maintained by intermittent reinforcement on a FR. The FR values initially were increased automatically and later the FR values were increased based on the analysis of the subject s responses. One subject was finally submitted to an extinction procedure of the lever pressing response. The availability of food also varied during experimental phases concomitantly with the manipulation of lever pressing and wheel running: food was initially available all the time, later food was available for 90 minutes daily, and, finally, it was available all the time again for some subjects.. Results indicated that the lever pressing that produced wheel running as a consequence was acquired and maintained for 4 of 5 subjects. Nevertheless these responses were emitted at low rates, and were acquired only after a long training. For one subject, the lever pressing response was acquired only when food was its consequence and was, then maintained when the consequence became wheel-running. Results also showed that rate of lever pressing and the number of wheel turns decreased as the value of fixed ratio increased, and that weight loss did not depend on the number of wheel turns, but seemed to depend on the time restriction of food availability. It is discussed that for 3 subjects the time restriction of food availability was an establishing operation for wheel-running